Kemahiran kejuruteraan perahu Melayu : keahlian jurubinanya berdasarkan teori Malakah Ibn Khaldun / Pisol Maidin and Thuraya Ahmad - Maidin, Pisol; Ahmad, Thuraya (Academy of Contemporary Islamic Studies, 2015)
One of the significant landmarks in a civilised society is the contribution of its artisans in producing artifacts. Not only that they could enrich the national cultural heritage but also would contribute in the growth of the nation's economy. Producing a cultural heritage like traditional boat needs a combination of selected woods, skilled craftsman and its related technological know-how. Apparently, this skilful craftsmanship could not sustain until today if it was not because of the craftsmanship itself and the conducive surroundings supporting the continuity of the art. Ibn Khaldun in his foremost masterpiece al-Muqaddimah emphasises the important role of craftsmen in building a civilisation. Through a prism of a Malakah theory introduced by Ibn Khaldun, this paper attempts to analyse the performance attributed to Malay carpenters in the engineering of boatbuilding and future prospect for the heritage. Apart from internal factors relating to the realm of carpenters and their tradition of the craftsmanship, other external environmental factors are obviously essential for the sustainability of the Malay boatbuilding craftsmanship.